Development of sweet potato (Ipomoea batatas) in acidified syrup packed in retortable pouch - King, Rhodessa Yu.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
This study aimed to develop a sweet potato in acidified syrup packed in retortable pouches. In the preliminary studies, syrup and acid concentration for the sweet potato in retortable pouch resulting into a high acid product was determined. The combination that produced a high acid product was 90oBrix syrup acidified to pH 3.5. In phase I, the lethality of the thermal process (95oC for 20 min) applied to the product was calculated. This resulted to D95 o C and F95 o C values of 10.58 and 52.91, respectively which were high compared to other studies. The high D95 o C and F95 o C may ensure microbial safety but may negatively affect the nutritional quality of the final product. In Phase II, the product created was evaluated. After one week of storage, the prouct had a pH of 4.48 and water activity of 0.899 classifying it as an acidified product. In addition, the sweet potato in acidified syrup packed in retortable pouches were determined to be microbially safe and consumer acceptable.
Thesis Classification: C
Thesis (B.S. in Food Technology)---University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Sweet potatoes